Continuous and discrete signals and systems - Soliman, Samir S. (Prentice-Hall, 1998)
Representing signals. Continuous-time systems. Fourier series. The fourier transform. The laplace transform. Discrete-time systems. Fourier analysis of discrete-time systems. The Z-transform. The discrete fourier transform. Design of analog and digital filters.